Phytochemicals, Signal Transduction, and Neurological Disorders - Farooqui, Akhlaq A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
x.
Chapter 1. Effects of life style and aging on the onset of neurological disorders -- Chapter 2. Beneficial effects of extra virgin olive oil (n-9 fatty acids) on neurological disorders -- Chapter 3. Beneficial effects of flaxseed oil (omega-3 fatty acids) on neurological disorders -- Chapter 4. Beneficial effects of flavonoids on neurological disorders -- Chapter 5. Beneficial effects of green tea catchins on neurological disorders -- Chapter 6. Beneficial effects of curcumin on neurological disorders -- Chapter 7. Beneficial effects of resveratrol on neurological disorders -- Chapter 8. Beneficial effects of Ginkgo biloba on neurological disorders -- Chapter 9. Beneficial effects of garlic components on neurological disorders -- Chapter 10. Beneficial effects of propolis on neurological disorders -- Chapter 11. Perspective and direction for future research on phytochemical in neurological disorders.
Keywords: Medicine; Neurosciences; Neurochemistry; Neurology; Biomedicine; Neurosciences; Neurology; Neurochemistry